2022
DOI: 10.3390/jfb14010003
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Polyelectrolyte Complexation for the Development of Adhesive and Bioactive Membranes Envisaging Guided Tissue Regeneration

Abstract: Mussels secrete protein-based byssal threads to tether to rocks, ships, and other organisms underwater. The secreted marine mussel adhesive proteins (MAPs) contain the peculiar amino acid L-3,4-dihydroxyphenylalanine (DOPA), whose catechol group content contributes greatly to their outstanding adhesive properties. Inspired by such mussel bioadhesion, we demonstrate that catechol-modified polysaccharides can be used to obtain adhesive membranes using the compaction of polyelectrolyte complexes (CoPEC) method. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…Moreover, ternary bioactive glass NPs (BGNPs) have been entrapped into the membrane to stimulate mineralization. Mechanical and in vitro studies revealed that the composition of this membrane possessed bioactive capabilities, enhancing mechanical and adhesive properties and increasing activity of SaOs-2 osteoblastlike cells, thus making this system suitable to improve bone regeneration [75]. In a similar way, Almeida et al [76] developed a multilayered film made of BGNPs as the inorganic phase, and HA and chitosan catechol conjugates as the organic phase.…”
Section: Nanomedical Applications Of Ha For Bone Regenerationmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, ternary bioactive glass NPs (BGNPs) have been entrapped into the membrane to stimulate mineralization. Mechanical and in vitro studies revealed that the composition of this membrane possessed bioactive capabilities, enhancing mechanical and adhesive properties and increasing activity of SaOs-2 osteoblastlike cells, thus making this system suitable to improve bone regeneration [75]. In a similar way, Almeida et al [76] developed a multilayered film made of BGNPs as the inorganic phase, and HA and chitosan catechol conjugates as the organic phase.…”
Section: Nanomedical Applications Of Ha For Bone Regenerationmentioning
confidence: 98%
“…Finally, adhesive and osteoconductive membranes made of HA have been developed for hard tissue regeneration. Fonseca et al [75], inspired by marine mussels' adhesive proteins, developed an HA/chitosan membrane modified with catechol groups using the compaction of polyelectrolyte complexes method, in order to enhance the adhesive properties of the assembled membranes. Moreover, ternary bioactive glass NPs (BGNPs) have been entrapped into the membrane to stimulate mineralization.…”
Section: Nanomedical Applications Of Ha For Bone Regenerationmentioning
confidence: 99%